2020
DOI: 10.1071/py18104
|View full text |Cite
|
Sign up to set email alerts
|

A uniform data set for determining outcomes in allied health primary contact services in Australia

Abstract: The project aim was to develop and implement a set of metrics to capture and demonstrate the performance of newly established allied health primary contact services. Selection of the metrics and performance indicators was guided by an existing state-wide data collection system and from a review of the published literature. The metrics were refined after consultation with a working group of health service managers and clinicians. The data collection and reporting framework were developed for use in allied healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The clinical outcome measures identified in this study are consistent with the standardised clinical outcomes assessments recommended in international practice guidelines (33,34) and in other studies of dietetics practice (24,29) . However, this study also identified how some dietitians use that data to demonstrate the relationship between dietitian activity (i.e., number of consultations) and resultant changes in client diet quality, improvement clinical measures (e.g., changes in weight or biochemical parameters) and subsequently satisfaction.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The clinical outcome measures identified in this study are consistent with the standardised clinical outcomes assessments recommended in international practice guidelines (33,34) and in other studies of dietetics practice (24,29) . However, this study also identified how some dietitians use that data to demonstrate the relationship between dietitian activity (i.e., number of consultations) and resultant changes in client diet quality, improvement clinical measures (e.g., changes in weight or biochemical parameters) and subsequently satisfaction.…”
Section: Discussionsupporting
confidence: 81%
“…Primary care dietitians have identified sophisticated processes to identify, generate, retain and expand the services they provide. Although business acumen (30) and aspects of identification and retention of clients to a clinical service has been discussed by others (29,31) , this study has identified the intricate relationship these aspects have to fundamental financial measures to ensure practice viability. Although, most participants had no formalised business training, many had upskilled by seeking specific training or mentoring.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations